WTO negotiations in the lead-up to Hong Kong : ACP priorities & challenges (2005)
Analyses seven key negotiating areas from the perspective of ACP countries outlining their priorities, the challenges they face and the likely outcomes. Concludes that if the Doha Round is to treat development concerns as more than just technical assistance and capacity-building, ACP countries must seize the opportunity to push special and differential treatment issues to the fore across all negotiating areas.
Keywords: TRADE NEGOTIATIONS